Integration between the South African and international bond markets : implications for portfolio diversification - Rabana, Phomolo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
International bond market linkages are examined using monthly bond yield data and total return indices on government bonds with ten years to maturity. The bond yield data covers a nineteen-year period from January 1990 to July 2008, while the bond total return index data covers a nine-year period from August 2000 to July 2008. The international bond markets included in the study are Australia, Canada, Germany, Japan, the United Kingdom, and the United States. The examination of international bond market linkages across these markets has important implications for the formulation of effective portfolio diversification strategies. The empirical analysis is carried out in three phases: the preliminary analysis, the principal component analysis (PCA), and the cointegration analysis. For each analysis and for each set of data the full sample period is first analysed and subsequently a five-year rolling window approach is implemented. Accordingly, this makes it possible to capture the time-varying nature of international bond market linkages. The preliminary analysis examines the bond market trends over the sample period, provides descriptive statistics, and reports the correlation coefficients between the selected bond markets. The PCA investigates the interrelationships among the bond markets according to their common sources of movement and identifies which markets tend to move together. The cointegration analysis is carried out using the Johansen cointegration procedure and investigates whether there is long-run comovement between South Africa and the selected bond markets. Where cointegration is found, Vector Error-Correction Models (VECMs) are estimated in order to examine the long-run equilibrium relationships in addition to their short-run adjustments over time. The empirical analysis results were robust, and overall integration between SA and the selected major bond markets remained weak and sporadic. In addition, the results showed that even after accounting for exchange rate differentials, international bond market diversification remained beneficial for a South African investor; and since international bond market linkages remained weak with no observable trend, international bond market diversification will remain beneficial for some time to come for a South African investor.
Keywords: Bond market; Bond market -- South Africa; Principal components analysis; International finance; Foreign exchange rates -- South Africa; Investments -- South Africa